MANAJEMEN LABA DAN RELEVANSI NILAI INFORMASI AKUNTANSI LABA DAN NILAI BUKU - Wibowo, Rahmat Haryo (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2010)
Management has an internal information and prospects of the company for more than investors. The availability of information held by the management than investors can lead to asymmetry of information and Opportunistic behavior can encourage management to select accounting policies in accordance with its interests through earnings management behavior. Investors will then choose the best information to make decisions. There are two general approaches used in assessing the performance of companies, ie earnings and book value approach.Income approach gives information perperiode company operations, while the book value approach gives information on the net value of the company's resources in the long term. In addition, the approach has more elements of profit earnings management compared to book value.There are indications of diminishing relevance value for each period due to various accounting-based trading activities and non-accounting and an indication of the increasing relevasi value. Some of the journals in this study tried to assert review whether there was an increase or decrease the relevance of the value of companies that conduct based on investor perceptions of earnings management.Keywords: value relevance, earning management